Point Omega : a novel - DeLillo, Don (Scribner, 2010)
Three unusual people--"defense intellectual" Richard Elster, who was involved in the management of the country's war machine; young documentary filmmaker Jim Finley, who is intent on documenting Elster's experience; and Elster's daughter Jessica, who behaves like an "otherworldly" woman from New York--train their binoculars on the desert landscape of California and build an odd, tender intimacy, something like a family. Then a devastating event throws everything into question.